2007
DOI: 10.1111/j.1540-6237.2007.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Who's Calling the Shots? Women Coaches in Division I Women's Sports*

Abstract: During the past 30 years, women have become an increasingly small proportion of coaches of women's sports. We test several explanations for why some institutions have women coaches and others do not. Copyright (c) 2007 by the Southwestern Social Science Association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…On the other hand, previous studies showed that only 7% of the Brazilian head coaches in different sports are female (Ferreira et al, 2013), which makes the women's basketball context a less unequal workplace regarding gender issues. Similarly, Welch and Sigelman (2007) found in Division I Women's Sports that women coaches are more prevalent in basketball than in three other team sports. These results suggest that women`s basketball is a sport in which women achieve a higher proportion of head coaching positions, compared to other women's sports.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…On the other hand, previous studies showed that only 7% of the Brazilian head coaches in different sports are female (Ferreira et al, 2013), which makes the women's basketball context a less unequal workplace regarding gender issues. Similarly, Welch and Sigelman (2007) found in Division I Women's Sports that women coaches are more prevalent in basketball than in three other team sports. These results suggest that women`s basketball is a sport in which women achieve a higher proportion of head coaching positions, compared to other women's sports.…”
Section: Discussionmentioning
confidence: 87%
“…For example, in the United States, 65.8% of the assistant coaches in women's basketball and 57.4% of the head coaches in women's basketball were female, according to a 2010 study (Walker & Bopp, 2010). In Division I Women's Sports, Welch and Sigelman (2007) found that women coaches are most prevalent in basketball compared to volleyball, soccer and softball. Although the representation of women in the sports workplace, and more specifically in basketball, is well-known in the United States, it may differ in other societies and cultural contexts, due to their particular social constructions and structural and symbolic gender arrangements.…”
mentioning
confidence: 99%
“…Overall women comprise only about 20.6% of head coaching positions (Carpenter and Acosta 2008). This pattern is unique, with no previous evidence of female occupations becoming largely male, as they have with regard to men coaching women's sports (Welch and Sigelman 2007).…”
Section: Justifying the Gender Gap In Coachingmentioning
confidence: 83%
“…Further, as adults, women face greater pressure to tend to home and family -even if they are working. Coaching may be regarded as incompatible with family life, especially long hours, travel, and inflexible time commitments (Acosta and Carpenter 1985;Everhart and Chelladurai 1998;Pastore, Inglis, and Danylchuk 1996;Welch and Sigelman 2007). Further research confirmed that human capital is a substantive contributor gender inequality in coaching (Knoppers, Meyer, Ewing, and Forrest 1989;Sagas and Cunningham 2004).…”
Section: Individual Approaches: Socialization and Human Capitalmentioning
confidence: 93%
See 1 more Smart Citation